2020
DOI: 10.1051/sicotj/2019042
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of HIV in patients undergoing lower limb Total Joint Arthroplasty (TJA) in South Africa

Abstract: Aim: The aim was to assess the seroprevalence of Human Immunodeficiency Virus (HIV) in non-haemophilic patients undergoing primary Total Joint Arthroplasty (TJA) at an academic hospital in South Africa. Methods: A retrospective review of all Total Hip Arthroplasty (THA) and Total Knee Arthroplasty (TKA) patients from January 2017 to December 2018 was conducted. All patients awaiting TJA were offered HIV screening and their demographic data were recorded. Consenting patients were tested or the refusal of testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Our results appear to reflect these data, with our HCV cohort having a 5.5% higher complication rate. It has also been shown that a majority of TJA HIV patients are younger on average and undergo THA (up to 79%) [11,21]. Our data do not reflect this surgical distribution, with half of HIV patients undergoing THA, but do reflect the age distribution with our HIV cohort averaging 56 years at age of surgery, much lower than the usual age of 68 years for THA [11,22].…”
Section: Discussioncontrasting
confidence: 71%
“…Our results appear to reflect these data, with our HCV cohort having a 5.5% higher complication rate. It has also been shown that a majority of TJA HIV patients are younger on average and undergo THA (up to 79%) [11,21]. Our data do not reflect this surgical distribution, with half of HIV patients undergoing THA, but do reflect the age distribution with our HIV cohort averaging 56 years at age of surgery, much lower than the usual age of 68 years for THA [11,22].…”
Section: Discussioncontrasting
confidence: 71%
“…The HIV percentage was comparative to that of a local study by Maharaj et al who quoted a figure of 6% seroprevalence in their patient population of 1 007 who had undergone TKA. 15 Of the 20 patients with HIV, only one complication occurred in a patient with OA who developed a DVT. This mirrors conclusions drawn in an article by Boylan et al, who found that HIV did not increase their TKA patients' overall risk of complications.…”
Section: Discussionmentioning
confidence: 98%
“…22 In a study of 1 007 TJA patients in South Africa, the seroprevalence of HIV in patients for THA was higher than the general population. 21 Furthermore, the 2018 International Consensus on Orthopaedic Infections determined that HIV is an independent risk for PJI. 23 This emphasises the importance of ASB in HIV-positive patients that may determine a further predisposing risk factor for PJI.…”
Section: Discussionmentioning
confidence: 99%